Building Regional Tourism Identity Through City Branding Logo - Muhammad Ikhsan Revadoni; Mugi Raharjo; Raden Hadapiningrani Kusumohendrarto (Jurnal Desain, 2024)
This analysis is a scientific analysis of the city branding logo to build the identity of a city. City branding logo Branding a city is one way to increase the attractiveness of tourists or visitors in the tourism sector the type of research used is a qualitative research method using non-interactive methods. The logo itself usually consists of typography (Logotype), and images (Logogram), it can even consist of the merger of several City Branding Logos that will be analyzed the city branding logo from Bantul, Jogja, and Solo, of the three objects of analysis all, have an influence on the development of city branding in each region. Based on the analysis, it can be concluded that each logo has a variety of philosophies related to what is in a city so that it can build the identity of the city.